ANALYSIS OF THE DESIGN OF A PREVENTIVE GUIDANCE AND COUNSELING PROGRAM TO REDUCE STUDENTS’ ACADEMIC ANXIETY - Fadhilah, Inda; Nugraha, Jaka (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the design of a preventive guidance and counseling program in efforts to reduce students’ academic anxiety. Academic anxiety is one of the psychological problems frequently experienced by students and has the potential to hinder academic achievement, learning motivation, and emotional well-being. A preventive approach in guidance and counseling services is considered strategic because it focuses on preventing problems from emerging before they develop into more complex disorders. This research employed a qualitative method with a descriptive-analytical design. Data were collected through in-depth interviews with guidance and counseling teachers, observations of service activities, and documentation studies of program planning. Data analysis was conducted through the stages of data reduction, data display, and thematic conclusion drawing. The findings indicate that an effective preventive guidance and counseling program design to reduce academic anxiety includes components such as students’ needs assessment, formulation of measurable objectives, development of service materials based on coping skills and stress management, collaborative implementation strategies involving subject teachers and parents, and continuous evaluation. The approaches applied in the program include classroom guidance services, group counseling, and emotional regulation skills training. These findings emphasize that a systematic, contextual, and needs-based program design can serve as an effective preventive strategy in minimizing academic anxiety and supporting the optimal academic and personal development of students.